Addressing progressive educational reforms: Fusing acquisition approaches and participation in Chinese entrepreneurship education. Issue 1 (March 2023) - Bell, Robin; Cui, Jun
Abstract: Entrepreneurship education and pedagogic reforms advocating the increased use of progressive educational methods have been promoted by the Chinese government. In practice, this has led to a fusion of the more traditional teaching approach and more progressive approaches. This has led to calls for entrepreneurship education to be contextualized within the Chinese context, against the backdrop of the progressive pedagogic reforms. This paper addresses this by exploring how Chinese educators are responding to directives encouraging progressive pedagogic entrepreneurship education, by applying the lens of Sfard's knowledge acquisition and participation-orientation learning metaphors. Interviews were conducted with fifteen educators and analysis of their narratives of practice was undertaken to identify knowledge acquisition and participation-orientation metaphors to elicit the approaches adopted in the classroom. The results indicate that both acquisition and participation approaches are adopted by educators, but in a way that reflects the traditional and cultural heritage that values knowledge. Educators still relied heavily on the transmission-acquisition metaphor, however the encouragement to introduce more progressive practices could be observed in two ways, the constructivist acquisition metaphor, and the participation metaphor. The former appeared more developed and the latter less so, although both are desirable in the light of the education reforms. Highlights: The implementation of more progressive teaching is done in a way that still incorporates Chinese educational tradition. The balancing of transmission-acquisition and constructivist-acquisition approaches challenges the conception of adopting either a traditional or a progressive approach to entrepreneurship education. Educators still rely heavily on transmission-acquisition, however more progressive practice can be found in the constructivist-acquisition and participation metaphors. The inclusion of constructivist-acquisition is more developed than the participation metaphor, although both are desirable in the light of education reforms.